2018
DOI: 10.1021/acs.jpcc.8b02617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Li2CoMn3O8 Nanostructures Synthesized by a Combustion Method on Montmorillonite K10 as a Potential Hydrogen Storage Material

Abstract: This paper outlines new design nanocomposites (Li 2 CoMn 3 O 8 /K10) for electrochemical hydrogen storage with an emphasis on the optimal conditions to achieve higher performance. Li 2 CoMn 3 O 8 /K10 nanocomposites were fabricated by loading different ratios of the Li 2 CoMn 3 O 8 (5%, 10%, and 20%) inside the montmorillonite K10. Electrochemical properties of the samples montmorillonite K10, Li 2 CoMn 3 O 8 , and the respective nanocomposites were studied by chronopotentiometry charge−discharge techniques in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Previous literature reported that coupling the magnetic and electric parameters can create magnetoelectric structures that can modify the energy storage ability through electrochemical methods. 57 The obtained hysteresis loop is a small, narrow hysteresis loop. The narrow hysteresis loop points small dissipated energy.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous literature reported that coupling the magnetic and electric parameters can create magnetoelectric structures that can modify the energy storage ability through electrochemical methods. 57 The obtained hysteresis loop is a small, narrow hysteresis loop. The narrow hysteresis loop points small dissipated energy.…”
Section: Resultsmentioning
confidence: 85%
“…On the other hand, the magnetic properties for as-fabricated nanocomposites are interesting due to the correlation between magnetic and electrical properties for electrochemical energy storage applications. Previous literature reported that coupling the magnetic and electric parameters can create magnetoelectric structures that can modify the energy storage ability through electrochemical methods . The obtained hysteresis loop is a small, narrow hysteresis loop.…”
Section: Resultsmentioning
confidence: 88%
“…The obtained peaks at 753, 691 and 537 cm −1 are related to bending bonds of Si–O-Al. The bonds at 1033 cm −1 refer to Si–O and OH vibrations in the halloysite units that appear at 791 cm −1 37 , 38 . Metal-oxide vibrations (465 and 539 cm −1 ) in cobalt ferrite and halloysite overlap with each other.…”
Section: Resultsmentioning
confidence: 99%
“…These chemical methods include ultrasonic-based precipitation, microwave-based precipitation, fuel-assisted sol-gel method, solvothermal and thermal treatment routes. [7][8][9][10] The metal oxide materials applied in the energy storage elds are comprehensive such as borate, vanadate, spinels, and perovskites. The central metals in these structures usually are cobalt, iron, nickel, magnesium, zinc, etc.…”
Section: Introductionmentioning
confidence: 99%